(untitled) - 1897-1943.; Knight, Eric; Dinklage, Peter; 1961-; 1932-2013.; Morton, Samantha; OToole, Peter; Sturridge, Charles; Lynch, John; Weinstein Company; Genius Entertainment ([New York], 2006)
The Carraclough family is forced to sell Lassie when they fall on hard times. On her journey of 500 miles, Lassie faces dangers, natural and human, and finds help in unexpected places as she returns to her home and the boy she loves.
Keywords: (Fictitious character); Juvenile drama; Lassie; Lassie; Drama; (Fictitious character); Juvenile drama; Dogs; Drama; Drama; England; Human-animal relationships; Collie; Adventure; Feature; Childrens; Feature; Animal; Feature; Drama; Childrens films; Films for the hearing impaired; Video recordings; Feature films; Action and adventure films